2021
DOI: 10.3389/fmars.2021.684634
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Habitat Characteristics of Aurelia sp. Polyps in a High-Latitude Fjord

Abstract: Causes and consequences of jellyfish bloom formation are subject to controversial discussions worldwide. While medusae have been studied to a broader extent, the knowledge on polyp stages of scyphozoans is limited thus hampering reliable prediction of jellyfish bloom formation. This study describes the occurrence, abundance, habitat characteristics and interactions of scyphozoan Aurelia sp. polyp colonies with other fouling organisms in intertidal and subtidal sectors of Trondheimsfjorden (Norway). In total, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Some potential competitors provide suitable microhabitat for polyps (e.g. Rekstad et al, 2021), and we have observed polyps on potential competitors in the past. However, in our data, there were very few polyps on potential competitors.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…Some potential competitors provide suitable microhabitat for polyps (e.g. Rekstad et al, 2021), and we have observed polyps on potential competitors in the past. However, in our data, there were very few polyps on potential competitors.…”
Section: Methodsmentioning
confidence: 72%
“…Whomersley and Picken, 2003), relative abundance of A. aurita polyps will decrease again, so that the increase in medusa abundance may be transient (Feng et al, 2017). However, sessile organisms including solitary ascidians and M. edulis provide suitable substrate for A. aurita polyps (Rekstad et al, 2021). There were few A. aurita polyps on these organisms in our experiment, but this is not the case in every year (M. Spencer, personal observation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, on the undersurface of a floating dock "Haiou" in Jiaozhou Bay, China, A. coerulea polyps were found to grow on the surfaces of many ascidians, bryozoans, and mussels (e.g., Styela clava, Watersipora subtorquata, and Mytilus galloprovincialis) besides on the areas without macro-fouling organisms (Figures 2B-E) like some other Aurelia spp. (Willcox et al, 2008;Di Camillo et al, 2010;Rekstad et al, 2021). However, in situ N. nomurai polyps on the plastic plates cultivated in Jiaozhou Bay were gradually covered by some neighboring fouling organisms (Figure 2F, Feng et al, 2017;Feng et al, 2018a).…”
Section: Specific Control Strategiesmentioning
confidence: 92%
“…Blooms caused by jellyfish, especially those of the class Scyphozoa, which have metagenic life cycles, have become a common phenomenon in recent years owing to various environmental pressures, including global climate change and anthropogenic activities (Purcell et al, 2007;Richardson et al, 2009;Purcell, 2012;Dawson et al, 2015;Quinones et al, 2018;Goldstein and Steiner, 2020;Rekstad et al, 2021;Riyas et al, 2021). The sudden or aberrant increase in jellyfish biomass has caused jellyfish disasters in several parts of the globe's oceans, affecting fisheries, and damaging the safety of nuclear power cooling-water systems (NPCSs), especially in Europe, Asia, and North America (Lucas and Dawson, 2014;Schiariti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%